The impact of poor data quality on the successful implementation of a customer-relationship management system in the banking environment: an application to a major South-African bank - Jafta, Zanele (University of the Free State, 2014)
Data quality is critical in business decisions, especially in formulating marketing, customer-relationship and sales strategies. Consistency and the quality of customer data are critical pillars for any business that is looking at introducing a client relationship management (CRM) system. For any successful CRM implementation, it is very important to have a single, integrated view of the customer even though the source data might come from different databases. This study explores the impact of poor data quality on the successful implementation of the customer-relationship management (CRM) system in one of the major banks in South Africa. The study will also determine data improvement and data-management frameworks in CRM systems.
Dissertation (MBA (Business Management))--University of the Free State, 2014
Keywords: Customer relations -- South Africa -- Management; Customer services; Bank management; Quality assurance; Banks and banking -- Quality control -- South Africa; Banks and banking -- South Africa